INFLUENCE OF METABOLIC THERAPY ON LIFE QUALITY IN PATIENTS WITH ATRIAL FIBRILLATION PAROXYSMS - I.M. Fushtey; S.L. Podsevahina; A.I. Palamarchuk; E.S. Chabanna (Сучасні медичні технології)
Abstract. The goal of the study was to investigate the effect of magnesium orotate as a part of complex therapy in sinus rhythm restoring in patients with AF paroxysm, as well as to evaluate its effectiveness and effect on LQo with long-term use.